2011
DOI: 10.2174/1876400201104010001
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Effects in Anaerobic Digestion – A Review

Abstract: This article reviews the experimental and theoretical studies conducted on the possible effects of oxygen in biogas generating anaerobic digesters. The interactions of oxygen with various biochemical processes associated with anaerobic digestion are discussed together with other relevant aspects. The conventional perception of oxygen being merely toxic in anaerobic digestion (AD) is refuted. Digesters can withstand significant levels of oxygenation without drastic negative impacts. Limited quantities of oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(77 citation statements)
references
References 131 publications
(367 reference statements)
0
76
0
1
Order By: Relevance
“…The effect of limited air supplied on the archaeal community structure and specific methanogenic activity (SMA) 3.3.1. The archaeal community structure change under microaerobic condition Methanogenic microorganisms are conventionally thought to be strictly anaerobic, tiny oxygen exposed may be lethal to the activity of methanogenic microorganisms [11,36]. However, it was reported methanogenic microorganisms belong to Methanobacterium and Methanosarcina all showed tolerance to limited oxygen [11,12].…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…The effect of limited air supplied on the archaeal community structure and specific methanogenic activity (SMA) 3.3.1. The archaeal community structure change under microaerobic condition Methanogenic microorganisms are conventionally thought to be strictly anaerobic, tiny oxygen exposed may be lethal to the activity of methanogenic microorganisms [11,36]. However, it was reported methanogenic microorganisms belong to Methanobacterium and Methanosarcina all showed tolerance to limited oxygen [11,12].…”
Section: Tablementioning
confidence: 99%
“…Recent studies have demonstrated the hydrolysis of AD could be enhanced by introducing limited amounts of oxygen (or air) directly into the anaerobic digester or during a pretreatment step [7,8]. On the one hand, facultative bacteria have a quick grow rate, consequently, more cellulose and protease hydrolytic enzymes will be produced, which will lead to higher hydrolysis rate [9,10] function under microaerobic condition with no or minor inhibitory effects [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The comprehensive review by Botheju and Bakke (2011) describe beneficial effects of adding limited oxygen during growth of methanogenic biomass. Methanogenic mixed cultures exposed to limited aeration still produce significant amounts of methane (Zitomer, 1995), and some low-aeration biomass exhibited 20% higher specific methanogenic activity (SMA) values than control cultures maintained anaerobically (Zitomer and Shrout, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, microaerobic pretreatment has been demonstrated to be a potential pretreatment method in several studies (Botheju and Bakke, 2011;Botheju et al, 2010;Jang et al, 2014;Johansen and Bakke, 2006;Lim and Wang, 2013;Mshandete et al, 2005). However, the mechanism of microaerobic pretreatment was still less known.…”
Section: Introductionmentioning
confidence: 99%
“…According to Charles et al (2009) and Zhu et al (2009), the higher facultative bacteria grow rate, more cellulase production and higher enzyme activity under microaerobic condition which then led to the higher hydrolysis could be the mechanism behind microaerobic pretreatment. Botheju and Bakke (2011) consequently produce more cellulose and protein hydrolytic enzymes. According to Lim et al (2014), the more diverse bacterial population and higher abundance of phylum Firmicutes under microaerobic condition led to the higher hydrolysis rates.…”
Section: Introductionmentioning
confidence: 99%